Influence of seasons and land-use practices on soil microbial activity and metabolic diversity in the “Montado ecosystem” - Costa, Dalila (2013)
The “Montado ecosystem” is important both economically and ecologically; this ecosystem is dominated by cork and holm oak trees (Quercus suber L. and Quercus rotundifolia Lam. respectively) combined with a rotation of crops/fallow/pastures. Diverse management strategies, deviating from the sustainable use of the ecosystem, have been implemented, from which arise some extreme situations of over-use or abandonment. To evaluate the effects of different soil use and management, namely extensive cropping, intensive pasture and abandonment, in the activity of soil microorganisms, dehydrogenase, acid phosphatase, b-glucosidase and urease activities, N-mineralization and nitrification rates were measured in different land-use practices, in different seasons (winter, spring and autumn). Also, the potential metabolic diversity was evaluated by analysis of community-level physiological profiles (CLPPs). Seasonal effects were evident with maximum activity occurring in rainy seasons (winter and autumn) and lower substrate utilization in winter. Significant correlations between most microbial parameters and soil water content reflect this seasonal effect. Although showing mainly a seasonal change, microbial parameters were able to distinguish the abandoned area, with a general low activity and differential exponential rates in the use of several substrates, such as amino acids, miscellaneous and polymers, probably associated with changes in organic matter quality.